(untitled) (INNOVATIVE ECONOMY, 2020)
Zaporozhets O.F. WAYS FOR IMPROVING THE QUALITY OF CUSTOMS SERVICES Purpose. The aim of the article is the development and substantiation of theoretical positions to improve the process of provision of customs services. Methodology of research. The information and theoretical basis of the study consisted of monographs, scientific works of domestic and foreign authors on the issues of quality management of customs services, normative legal acts of Ukraine. The research was carried out on the basis of the use of methods: axiomatic – to determine the essence of customs services; abstract and logical – to generalize theoretical aspects and formulate the final conclusions on the formation of scientific approaches to improve the quality of customs services; analogies – with the improvement of the conceptual and categorical apparatus of the customs business. Findings. The ways of raising the level of quality of customs services, which will ultimately contribute to the implementation of EU standards for customs clearance by the State fiscal customs control and customs clearance of goods and vehicles, are proposed; improving the quality of customs procedures; reducing the level of corruption; introduction of a mechanism for monitoring the activities of customs officers; introduction of programs of motivation of honest customs officers. Originality. The theoretical positions concerning development of the system of quality management of customs services are substantiated and developed by allocating the main directions of improving the quality of customs services in the conditions of reforming fiscal bodies. The concept and categorical apparatus of the customs business has been improved. Practical value. The results obtained during the research can be used in the process of further development of conceptual approaches to reforming the customs business in Ukraine. Key words: customs; level of quality of customs services; management; fiscal service; intermediary.